Clinical manifestations and outcome of SARS-CoV-2 infections in children and adolescents with rheumatic musculoskeletal diseases: data from the National Paediatric Rheumatology Database in Germany. Issue 2 (26th July 2021) - Sengler, Claudia; Eulert, Sascha; Minden, Kirsten; Niewerth, Martina; Horneff, Gerd; Kuemmerle-Deschner, Jasmin; Siemer, Caroline; Berendes, Rainer; Girschick, Hermann; Hühn, Regina; Borte, Michael; Hospach, Anton; et al.
Abstract : Objectives: This study aimed to investigate the clinical manifestations, course and outcome of SARS-CoV-2 infection among children and adolescents with rheumatic and musculoskeletal diseases (RMD). Due to their underlying disease as well due to therapeutic immunosuppression, these patients may be at risk for a severe course of COVID-19 or for a flare of the underlying disease triggered by SARS-CoV-2 infection. Methods: Demographic, clinical and treatment data from juvenile patients with RMD as well as data about SARS-CoV-2 infection like test date and method, clinical characteristics, disease course, outcome and impact on the disease activity of the RMD were documented on a specific SARS-CoV-2 questionnaire implemented in the National Paediatric Rheumatology Database (NPRD) in Germany. The survey data were analysed descriptively. Results: From 17 April 2020 to 16 February 2021, data were collected from 76 patients (52% female) with RMD and laboratory-proven SARS-CoV-2 infection with median age of 14 years, diagnosed with juvenile idiopathic arthritis (58%), autoinflammatory (24%) and connective tissue disease (8%). Fifty-eight patients (76%) received disease-modifying antirheumatic drugs (DMARDs), 41% biological DMARDs and 11% systemic glucocorticoids. Fifty-eight (76%) had symptoms of COVID-19. Disease course of SARS-CoV-2 infection (classified as asymptomatic, mild, moderate, severe, life-threatening) was mild and outcome of COVID-19 (classified as recovered, not yet recovered, permanent damage or deceased) was good (recovered) in the majority of patients. Two patients were hospitalised, one of whom required intensive care and died of cardiorespiratory failure. In 84% of SARS-CoV-2-positive patients, no relevant increase in disease activity of the RMD was observed. Conclusions: In our cohort, SARS-CoV-2 infection in juvenile patients with RMD under various medications was mild with good outcome in the majority of cases and does not appear to have a relevant impact on disease activity of the underlying condition.